Performance metrics for the prediction of link and path availability in VANETs - Muhammed Yusof, Zulkefli; Flint, James A. (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
In this paper metrics are produced which may be used for performance enhancement in Vehicular ad-hoc networks (VANETs) protocols. The method described makes use of the concept of link availability estimates which are produced on an individual link basis and which may be combined by multiplication to produce a quality metric for the whole route. The technique is discussed in the context of the Ad hoc On-demand Distance Vector (AODV) routing method.